Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jand.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

¡Cocinar Para Su Salud!: Randomized Controlled Trial of a Culturally Based Dietary Intervention among Hispanic Breast Cancer Survivors

Abstract: BACKGROUND There is a need for culturally-relevant nutrition programs targeted to underserved cancer survivors. OBJECTIVE To examine the effect of a culturally-based approach to dietary change on increasing fruit/vegetable intake and decreasing fat intake among Hispanic breast cancer (BC) survivors. DESIGN Participants were randomized to intervention (IG) and control (CG) groups. Diet recalls, detailed interviews, fasting blood, and anthropometric measures were collected at baseline, 3-, 6- and 12-months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…This is an important concept to acknowledge in designing future interventions as group counseling may initially appear to be a way of increasing peer support and thus intervention adherence. However, in two previous studies of breast cancer survivors, results indicated that group dietary counseling sessions did not lead to an increase fruit and vegetable intake [26, 27]. In comparison, in a mixed cancer cohort study patients who received individualized dietary counseling during treatment reported better weight maintenance and higher intakes of adequate protein and calories as compared to those in the control arm who did not receive individualized counseling [28].…”
Section: Discussionmentioning
confidence: 97%
“…This is an important concept to acknowledge in designing future interventions as group counseling may initially appear to be a way of increasing peer support and thus intervention adherence. However, in two previous studies of breast cancer survivors, results indicated that group dietary counseling sessions did not lead to an increase fruit and vegetable intake [26, 27]. In comparison, in a mixed cancer cohort study patients who received individualized dietary counseling during treatment reported better weight maintenance and higher intakes of adequate protein and calories as compared to those in the control arm who did not receive individualized counseling [28].…”
Section: Discussionmentioning
confidence: 97%
“…From the outset, the research team was aware that the population of Latina breast cancer survivors living in Northern Manhattan is highly diverse in terms of national background, socioeconomic status, and level of acculturation. 15 , 42 , 43 The intervention was designed to be broadly applicable to this population. Written, informed consent was obtained for participants who engaged in the pilot testing (n = 19).…”
Section: Methodsmentioning
confidence: 99%
“… 11 - 13 Our prior work has shown low fruit/vegetable intake and low physical activity in Latina breast cancer survivors living in Northern Manhattan. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, AOG met HG, a cancer epidemiologist and cancer prevention scientist, when she was a faculty member at Columbia University’s Mailman School of Public Health. With funding from the National Cancer Institute (NCI), they developed AOG’s program into a formal curriculum and tested it in the Cocinar Para Su Salud (Cook for Your Health) study (ClinicalTrials.gov NCT01414062) [ 16 , 17 ]. In 2012, AOG founded the Cook for Your Life website [ 15 ], recognizing that sharing tips and recipes online could broaden the reach to patients with cancer and survivors worldwide.…”
Section: Introductionmentioning
confidence: 99%